(untitled) (Journal of the College of Basic Education, 2022)
This research is concerned with studying the counterpoint between language and design in the form of the industrial product, by employing counterpoint in the constructive design process, on which the structural and aesthetic construction of the industrial product is based. In the designs of industrial products, as it was possible to detect the existence of rhetorical arts in the design language, such as counterpoint, and study the possibility of its application, so it is necessary to focus on the concept of counterpoint as a new art that presents itself within the process.